Determinan Motivasi Berpartisipasi Mahasiswa Bidang Kesehatan dalam Penanggulangan Bencana - Shylvana Adella*; Agussabti Agussabti; Mudatsir Mudatsir (Jurnal Pendidikan Sains Indonesia, 2021)
Indonesia has a high risk of disaster hazards. According to BNPB (National Disaster Management Agency), in the past 10 years the incidence of disasters in Indonesia's territory has increased. Tornadoes, floods, landslides and earthquakes have become the disasters with a high incidence rate. Health workers are an important part of disaster management, both during emergency response and during other disaster management phases. Lack of capacity of health workers can occur, the potential resource available to meet the shortage of health personnel at the time of a disaster is students in the health sector. This study aims to examine the influence of internal variables (respondens’ gender, study period, disaster experiences, disaster knowledge, students’ organization experiences, volunteering experiences, training/skills, religiosity) and external variables (family support, university support, trust in organizations disaster management, and the type of disaster faced) on the students’ participation motivation in the health sector involved in disaster management. The population of this study was the health department students (general medicine, nursing, psychology and dentistry) of Syiah Kuala University, Banda Aceh, Indonesia. A sample of 260 health students was taken using the quota sampling method. The data obtained through an online questionnaire distributed from April to June 2020. The gathered data was analyzed using the multiple regression statistical method. The results showed that the students’ participation motivation in disaster management activities is between low to moderate. There are only three factors that influence this students’ participation motivation, namely study period, training / skills and university support.